Effects of Scleral Contact Lenses for Keratoconus Management on Visual Quality and Intraocular Pressure - Formisano M; Franzone F; Alisi L; Pistella S; Spadea L (Dove Medical Press, 2021)
Martina Formisano, Federica Franzone, Ludovico Alisi, Santino Pistella, Leopoldo Spadea Eye Clinic, Department of Sense Organs, University of Rome Sapienza, Policlinico Umberto I, Rome, ItalyCorrespondence: Leopoldo SpadeaEye Clinic, Policlinico Umberto 1, “Sapienza” University of Rome, Via Benozzo Gozzoli 34, Rome 00142, ItalyTel +039 06 519 3220Fax +39 06 8865 7818Email leopoldo.spadea@uniroma1.itPurpose: To evaluate the visual acuity level achieved by scleral contact lens (CL) fitting in patients affected by keratoconus and to evaluate possible intraocular pressure (IOP) changes during the scleral CL wear using a transpalpebral tonometer.Methods: In a prospective case series a comparison was made between visual acuity obtained with glasses, RGP and 16.8mm diameter scleral CL in 30 consecutive patients affected by keratoconus. IOP was tested during scleral CL wear by transpalpebral Diaton Tonometer (DT) and also by Goldmann Applanation Tonometer (GAT) before and after scleral CL wear.Results: The mean logMAR visual acuity improved from 0.2± 0.25SD with glasses and 0.1± 0.02SD with RGP, to − 0.002± 0.041SD when using the scleral CL (p< 0.05). The mean IOP value before scleral CL wear was 12.93mmHg± 2.20SD when measured with GAT and 7.85mmHg± 2.27SD when measured with DT. During scleral CL wear, IOP was assessed through DT, with a mean value of 8.86mmHg± 2.36SD; values were stable after 8 hours of scleral CL use. Immediately after scleral CL removal, the mean IOP measured with GAT was 12.85mmHg ± 2.40SD and the mean IOP measured with DT was 7.66mmHg± 1.88SD. Therefore, during scleral CL wear, it was evidenced a small but statistically significant increase of the mean IOP value (1.01mmHg; p< 0.01), with a reversion to values prior to application when scleral CL was removed.Conclusion: Scleral CLs remarkably improved visual acuity in keratoconus patients when compared to glasses or RGP contact lenses. Even if it was evidenced a small increase of the mean IOP value during their wear, it may not be significant in otherwise healthy eyes. Statistical analysis demonstrated good agreement between GAT and DT but their numerical values presented a constant gap, that should be taken into account when there is a need to relate the DT values to the reference ones.Keywords: keratoconus, higher-order aberrations, IOP, scleral contact lens